2012
DOI: 10.1021/jf3031875
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Association Study of Resistant Starch (RS) Phenotypes in a Barley Variety Collection

Abstract: Barley is primarily grown for feed and malt, but in some regions of the world it is also considered to be a staple food. Some barley types such as high-amylose barley have also gained importance as health-promoting foods. Starch that is not readily digested in the upper mammalian gastrointestinal system, or resistant starch (RS), is considered to be valuable because it prevents some diet-related diseases such as colon cancer. RS was quantified in a diverse collection of 209 spring barley varieties released in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 57 publications
0
19
1
Order By: Relevance
“…GWAS have identified allelic polymorphisms for important agronomic traits in cereal crops [2832], including alleles responsible for variation in grain composition of rice [30, 32], maize [3336], and barley [37, 38]. Linkage and association studies have identified several loci controlling sorghum grain composition [3943], and the identification of the gene underlying the waxy mutation has been fine mapped to 1.8 Mb on chromosome 10 [44], but more work needs to be done to precisely identify genes responsible for natural variation of grain composition.…”
Section: Introductionmentioning
confidence: 99%
“…GWAS have identified allelic polymorphisms for important agronomic traits in cereal crops [2832], including alleles responsible for variation in grain composition of rice [30, 32], maize [3336], and barley [37, 38]. Linkage and association studies have identified several loci controlling sorghum grain composition [3943], and the identification of the gene underlying the waxy mutation has been fine mapped to 1.8 Mb on chromosome 10 [44], but more work needs to be done to precisely identify genes responsible for natural variation of grain composition.…”
Section: Introductionmentioning
confidence: 99%
“…While the RS content in common cereals is very low (mostly below 3%) (Shu et al, 2006), a few cereal varieties and accessions with a high RS content have been reported, e.g. 15 barley varieties had RS above 11% (Shu et al, 2012) and a series of rice mutants with an enhanced RS content have been obtained through mutation breeding (Shu et al, 2009). This suggests that RS might potentially not be metabolized in cereals and therefore that a high content of RS might have a negative effect on germination and seedling development.…”
Section: Introductionmentioning
confidence: 99%
“…Members of the GT family and glycoside hydrolase were also found to be responsible for resistant starch accumulation in a recent GWAS of barley (Shu et al, 2012). That indicated these genes might affect synthesis of starch molecular components indirectly by regulating other pathways in the metabolic network through the same substrates especially those depending on UDP-glucose (Figure 4).…”
Section: Discussionmentioning
confidence: 99%